2015
DOI: 10.1371/journal.pone.0120156
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Recombinant Laccase from the Yeast Yarrowia lipolytica and Its Application in the Hydrolysis of Biomass

Abstract: A modified thermal asymmetric interlaced polymerase chain reaction was performed to obtain the first yeast laccase gene (YlLac) from the isolated yeast Yarrowia lipolytica. The 1557-bp full-length cDNA of YlLac encoded a mature laccase protein containing 519 amino acids preceded by a signal peptide of 19 amino acids, and the YlLac gene was expressed in the yeast Pichia pastoris. YlLac is a monomeric glycoprotein with a molecular mass of ~55 kDa as determined by polyacrylamide-gel electrophoresis. It showed a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 40 publications
4
24
1
Order By: Relevance
“…Recombinant CpLcc1 laccase was strongly inhibited by 1 mM sodium azide and 1 mM SDS by 90.12% and 84.90%, respectively, while 0.1 mM sodium azide and 1 mM L-cysteine also caused 55.62% and 25.34% inhibition, respectively (Table 5). These results were in accordance with the results from previous reports (Garcia et al, 2007;More et al, 2011;Kalyani et al, 2015).…”
Section: Effect Of Inhibitors On the Activity Of The Recombinant Laccsupporting
confidence: 93%
See 1 more Smart Citation
“…Recombinant CpLcc1 laccase was strongly inhibited by 1 mM sodium azide and 1 mM SDS by 90.12% and 84.90%, respectively, while 0.1 mM sodium azide and 1 mM L-cysteine also caused 55.62% and 25.34% inhibition, respectively (Table 5). These results were in accordance with the results from previous reports (Garcia et al, 2007;More et al, 2011;Kalyani et al, 2015).…”
Section: Effect Of Inhibitors On the Activity Of The Recombinant Laccsupporting
confidence: 93%
“…Thus, in the present study, effect of temperature on the enzyme activity was analyzed against ABTS between 20 °C and 90 °C. Consistent with a previous report (Kalyani et al, 2015), the optimum temperature of the recombinant enzyme CpLcc1 was found as 70 °C (Figure 6a). The half-life of its activity (t 1/2 ) was longer than 8 h at both 30 °C and 40 °C and it was 30 min at 50 °C (Figure 6b).…”
Section: Effect Of Temperature and Ph On The Activity Of The Recombinsupporting
confidence: 92%
“….2) is a blue copper oxidase with a broad range of substrates (Kalyani et al 2015), varying from organic to inorganic compounds such as diphenols, aromatic amines, polyphenols (Hoegger et al 2006;Rivera-Hoyos et al 2013;Sharma et al 2007), and Mn 2+ (Brouwers et al 1999). The reactions of laccase are mediated by a one-electron transfer mechanism (Thurston 1994).…”
Section: Open Accessmentioning
confidence: 99%
“…1 g of activated sludge was mixed with 9 ml of normal saline and was shaken for 1 h with glass beads on a horizontal shaker. This suspension was centrifuged and supernatant was used for assaying the activity using 2 mM ABTS at different pH (5,6,7,8) and temperatures 37-75°C. Controls were set up using autoclaved sludge suspension.…”
Section: Phenol Oxidase Activity In Sludgementioning
confidence: 99%
“…Laccase is a multicopper enzyme found in a wide range of taxa including plants, fungi, bacteria, insects and bacteria. Recently, laccase was also reported in yeast [8]. It performs reactions in ecofriendly manner, requires only oxygen to catalyze the oxidation of phenolic compounds and produces water as by product.…”
Section: Introductionmentioning
confidence: 99%